Morpho-metabolic post-surgical patterns of non-infected prosthetic heart valves by [18F]FDG PET/CTA: "normality" is a possible diagnosis. (20th September 2019) - Roque, Albert; Pizzi, María N; Fernández-Hidalgo, Nuria; Permanyer, Eduard; Cuellar-Calabria, Hug; Romero-Farina, Guillermo; Ríos, Remedios; Almirante, Benito; Castell-Conesa, Joan; Escobar, Manuel; Ferreira-González, Ignacio; Tornos, Pilar; et al.
Abstract: Aims: To define characteristic PET/CTA patterns of FDG uptake and anatomic changes following prosthetic heart valves (PVs) implantation over time, to help not to misdiagnose post-operative inflammation and avoid false-positive cases. Methods and results: Prospective evaluation of 37 post-operative patients without suspected infection that underwent serial cardiac PET/CTA examinations at 1, 6, and 12 months after surgery, in which metabolic features (FDG uptake distribution pattern and intensity) and anatomic changes were evaluated. Standardized uptake values (SUVs) were obtained and a new measure, the valve uptake index (VUI), (SUVmax–SUVmean)/SUVmax, was tested to homogenize SUV results. In total, 111 PET/CTA scans were performed in 37 patients (19 aortic and 18 mitral valves). FDG uptake was visually detectable in 79.3% of patients and showed a diffuse, homogeneous distribution pattern in 93%. Quantitative analysis yielded a mean maximum standardized uptake value (SUVmax) of 4.46 ± 1.50 and VUI of 0.35 ± 0.10. There were no significant differences in FDG distribution or uptake values between 1, 6, or 12 months. No abnormal anatomic changes or endocarditis lesions were detected in any patient during follow-up. Conclusions: FDG uptake, often seen in recently implanted PVs, shows a characteristic pattern of post-operative inflammation and, in the absence of associated anatomic lesions, could be considered a normal finding. These features remain stable for at least 1 year after surgery, so questioning the recommended 3-month safety period. A new measure, the VUI, can be useful for evaluating the FDG distribution pattern.